Analisa Dampak Penerapan Aplikasi Jatonic terhadap Efisiensi dan Akuntabilitas Manajemen Kas Kecil - Hardani Hardani; Ninuk Riesmiyantiningtias; Hariyanto Hariyanto (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
Advances in digital technology have brought about significant changes in the world of accounting, where processes that were previously performed manually have now shifted to fully automated systems supported by specialized software. Currently, PT. Abadi Jaya has implemented a computerized accounting system, which automates the recording, management, and reporting of the company’s financial data. Manual petty cash management is inefficient and lacks accountability in reporting. PT. Abadi Jaya faces several issues, including errors in inputting petty cash expenditure amounts due to human error, and limited access to the Jatonic application, which is restricted to specific departments. and delays in reporting. Research Objectives: To analyze the implementation of the Jatonic application; to identify factors influencing the smoothness of petty cash management processes; to identify challenges faced by the company in petty cash management. The method used was a case study at PT. Abadi Jaya employed a descriptive qualitative approach, including primary data collected through interviews, observations, and documentation of recording processes before and after implementation. The research results indicate that the Jatonic application significantly reduces reconciliation processing time, eliminates the risk of manual input errors, and saves administrative costs, representing an increase in efficiency. On the other hand, the application’s audit trail and multi-level approval features have successfully enhanced transparency and clarified accountability for each expenditure, thereby ensuring strong financial accountability. With updates and improvements in technical aspects and oversight, this system can deliver greater benefits for the company’s operations..